1995
DOI: 10.1093/oxfordjournals.humrep.a136027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and preventing inherited disease: The use of first polar bodies for preimplantation diagnosis of aneuploidy

Abstract: A large proportion of patients undergoing in-vitro fertilization (IVF) are aged > or = 35 years. It has been estimated that in this age group, 50% of embryos are chromosomally abnormal, with aneuploidy being the major contributing factor. Since the origin of most aneuploidies is maternal meiosis I non-disjunction, unfertilized oocytes could be safely screened for aneuploidy by analysing their first polar bodies. To determine the feasibility of first polar body aneuploidy analysis, polar bodies were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…S8b,c), we observed localization of DNA within fragments (indicated by white arrow in DAPI images and solid black arrow in differential interference contrast (DIC)/merged images). We also observed fragments negative for DAPI staining (shown by dashed black arrow) adjacent to DAPI-positive fragments, indicating that some but not all fragments contain nuclear DNA and eliminating the possibility that these fragments were polar bodies, which should have degenerated or initiated degeneration by this stage of development23 (Supplementary Fig. S8a).…”
Section: Resultsmentioning
confidence: 92%
“…S8b,c), we observed localization of DNA within fragments (indicated by white arrow in DAPI images and solid black arrow in differential interference contrast (DIC)/merged images). We also observed fragments negative for DAPI staining (shown by dashed black arrow) adjacent to DAPI-positive fragments, indicating that some but not all fragments contain nuclear DNA and eliminating the possibility that these fragments were polar bodies, which should have degenerated or initiated degeneration by this stage of development23 (Supplementary Fig. S8a).…”
Section: Resultsmentioning
confidence: 92%
“…Although PCOS patients are typically characterized by producing an increased number of oocytes, they are often of poor quality, leading to lower fertilization, cleavage and implantation rates, and a higher miscarriage rate (Sengoku et al ., 1997; Ludwig et al ., 1999; Mulders et al ., 2003; Heijnen et al ., 2006; Weghofer et al ., 2007; Sahu et al ., 2008; Boomsma et al ., 2008). This evidence raises the issue that poor oocyte and embryo quality may contribute to increased aneuploidy rates (Munné et al ., 1995; Gianaroli et al ., 2003, 2007). However, recent data suggest that women with PCOS yield higher numbers of oocytes and produce more euploid embryos in IVF, but still result in lower pregnancy and increased miscarriage rates, which are not genetically associated with an increased risk for embryonic aneuploidy (Weghofer et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PGS is performed in samples biopsied from polar bodies [10-13], cleavage embryos [14,15] or blastocysts [16,17]. It has been found that blastocysts have less mosaicism than cleavage embryos, thus most laboratories prefer blastocyst biopsy, in which multiple cells from the trophectoderm (TE) are biopsied and used for screening [8,9].…”
Section: Introductionmentioning
confidence: 99%